PHARMACODYNAMIC OF METFORMIN IN TYPE 2 DIABETES MELLITUS PATIENTS: REVIEW OF THE PRKAA2 AND SLC22A3 GENES - Sakura Muhammad Tola; Sultana MH Faradz; Ahmad Rusdan Handoyo Utomo; Samsul Mustofa (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
Type 2 diabetes mellitus (type 2 DM) is a disease including on metabolic disorder that characterized by an increase in glucose levels above normal. This glucose increase is caused by reduced insulin function which can be in the form of abnormalities in insulin secretion, impaired insulin action in peripheral tissues, or both. Metformin is one of the recommended therapies for type 2 DM. AMPK is the main pathway of metformin's mechanism. AMPKa2 encoded by PRKAA2 gene is an AMPK subunit that plays an important role in AMPK activation. OCT3 encoded by SLC22A3 plays a role in the metformin transport mechanism. OCT3 is needed in the metformin pharmacokinetic like absorption and elimination, this process determines metformin bioavailability, clearance, and its pharmacological effects. Mutations in PRKAA2 and SLC22A3 cause variations in the pharmacodynamic effects and pharmacokinetic of metformin in individuals directly. These changes will ultimately affect the effectiveness of metformin in type 2 DM patients.